Some defaults are deeper than others: Understanding long-term mortgage arrears - Kelly, Robert; McCann, Fergal (Journal of Banking & Finance, 2016)
The 2007–2008 financial crisis yielded a significant number of delinquent mortgage loans, which ordinarily would have faced foreclosure and repossession. However, given the negative externalities of repossession, policy response has shifted towards forbearance and mortgage modification, which has led to longer spells in default for delinquent mortgage holders. It is therefore imperative to move beyond binary models of default towards an understanding of the factors that drive the depth of default spells. Exploiting a highly detailed dataset on financially distressed households in Ireland in 2012 and 2013, we are able to identify the impact of a range of current household-level factors, generally not available in loan-level studies of mortgage default, on the probability of entering early and deep states of mortgage default. Our results suggest that high loan-to-value ratios, consumer credit growth, shocks to mortgage affordability and unemployment should all trigger serious concerns among policy makers regarding subsequent stability in the mortgage market, with these measures all shown to have differentially large impacts on entry to deep, relative to early-stage arrears.